Caracterização genotípica de amostras de Leishmania spp. isoladas de área endêmica para Leishmaniose Visceral Canina no estado de São Paulo - Coiro, Carla Janeiro [UNESP] (2014)
The canine visceral leishmaniasis (LCV), known as American visceral leishmaniasis (LVA) or kala-azar is a anthropozoonosis caused by the flagellate protozoan of the genus Leishmania, with worldwide distribution. In Brazil, the agent responsible for the disease is Leishmania (Leishmania) chagasi, transmitted by the bite of the female of the species Lutzomyia longipalpis, and the main reservoir is the domestic dog. It is a severe systemic disease, with chronic and slow course and complex diagnostic. Among the strategies for control of LVC are the canine serological survey, with the elimination of reagents dogs and different techniques can be used to diagnose this disease. Many advances have occurred in recent years, but about the tests available for diagnosis, none had 100% sensitivity and specificity. In this context, this project aimed to determine the prevalence of antibodies to L. chagasi in 164 dogs captured by the CCZ, Bauru, SP, epidemic area for LVC, to compare the techniques of indirect immunofluorescence, enzyme immunoassay (ELISA) and direct agglutination (DAT) to determine the parasite burden by PCR in real time from peripheral blood puncture, popliteal lymph node and bone marrow of animals serologically positive, and identify potential genotypic variants of Leishmania. spp. from the sequencing in order to contribute to the diagnosis of canine visceral leishmaniasis, from the analysis obtained for the different tests as well as for assessment of symptoms presented by the animals. The sensitivity shown by DAT and ELISA with IFA as the gold standard were respectively, 94% and 87%, while specificity was 28% and 93%. Of the total sample of blood, lymph node and bone marrow subjected to PCR genus and species-specific, 20 were positive only for gender, and these were sequenced and characterized, yielding cleavage bands profile and common sequences belonging to the species L.donovani complex